Outcome of recipients of human leukocyte antigen incompatible kidney transplants who underwent desensitization at King Fahad Specialist Hospital, Dammam, Saudi Arabia - Mohammed Abdulrahim Idris; Akhtar Hossain; Mohammed Abdulrahman Muntasir; Adnan Marmi; Ahmed Abdulfattah Aldajani; Yousef Mohammed Aljamaan; Mahmood Akhtar; Abdulrahman Housawi (Saudi Journal of Kidney Diseases and Transplantation, 2017)
In patients whom are highly sensitized immunologically, the benefit of kidney transplantation can be extended to this population through the utilization of organs from human leukocyte antigen incompatible (HLAi) donors. This retrospective observational study was designed to identify the incidence and predictors of acute antibody-mediated rejection/acute cellular rejection (AMR/ACR) in our kidney recipients from living kidney donors (sensitized and those with low immunologic risk). This single-center study has been conducted at King Fahad Specialist Hospital, Dammam (KFSH-D), Saudi Arabia; during the period of September 2008- August 2013. All eligible recipients of living donor kidneys during the study period were included (n = 213) in the study. Over 60% of patients in the study were females. Thirty of the 213 kidneys were from HLAi donors. During the follow-up period (median follow-up time = 16 months; 3–27 months), the incidence rate of ACR among HLA compatible (HLAc) and HLAi groups was 22.2% and 16.7%, respectively (P >0.05). The incidence rate of AMR was 2.6% in HLAc group and 16.7%in the HLAi group (P<0.05). The significantly higher incidence of AMR in HLAi group can be explained by the presence of the donor-specific antibodies in weak titers. These results are consistent with studies from similar populations in published literature. However, the relatively small number and short duration of the study are considered, and longer follow-up of this population will be needed for conclusions on the sustainability of our findings.